In-vitro evaluation of botanicals and fungicides against Bipolaris sorokiniana, causing spot blotch of wheat - Magar, Prem Bahadur; Baidya, Suraj; Koju, Rabina; Adhikary, Sagar (Journal of Agriculture and Natural Resources, 2020)
Spot blotch disease of wheat caused by Bipolaris sorokiniana; is one of the most concerning disease in warm and humid regions of Nepal due to its widespread prevalence and increasing severity. An in-vitro experiment was conducted to evaluate the efficacy of different botanicals and fungicides against Bipolaris sorokiniana, in National Plant Pathology Research Centre’s laboratory at Khumaltar, Lalitpur in 2019. The experiment was done in completely randomized design with three replications by poison food technique. Five botanicals viz. neem, garlic, eucalyptus, bojho and asuro at three different concentrations (5%, 10% and 15%) and eight fungicides viz. sectin, curex, bavistin, vacomil plus, saaf, sajha, criptan and tilt at three concentration levels (25 ppm, 50 ppm and 100 ppm) except curex (50 ppm, 100 ppm and 200 ppm) were used to evaluate the effect on the radial mycelial growth and mycelial growth inhibition percentage of the pathogen. The different botanical extracts and fungicides in different concentrations inhibited the mycelial growth of fungus significantly (p<0.01). The highest mycelial growth inhibition percentage was found by the application of garlic clove extract (52.85%) at 15% which was followed by bojho (52.48%) at 15% concentration. While tilt was found effective fungicide which completely inhibits the mycelial growth at all concentrations. Also, fungicides viz. sajha (79.78%), saaf (73.59%) and sectin (70%), at 100 ppm were found effective in controlling the pathogen as compare to others. Mycelial growth inhibition of the fungus was found to be increased with the increase in concentrations of botanicals and fungicides.